1998
DOI: 10.1111/j.1440-1746.1998.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 expression as a prognostic marker in patients with hepatocellular carcinoma

Abstract: Ki-67 expression in tumours has been shown to be associated with prognosis in patients with hepatocellular carcinoma (HCC). In this study, primary HCC samples were obtained from 67 patients undergoing surgical resection. None of these patients had been subjected previously to any other form of therapy, such as arterial embolization or chemotherapy. Histologically normal liver tissues from liver resection for metastatic colon cancer were taken as controls (n = 8). Monoclonal antibody against Ki-67 was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…However, the present findings cannot be underestimated because uncontrolled cell growth plays a particularly integral role in the progression of HCC. Indeed, several reports have shown that the expression of proliferating cell nuclear antigen (PCNA) and Ki-67 is significantly associated with HCC relapse (25,26). This is in contrast to colon cancer, where proliferative activity alone appears not to result in fatal events (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present findings cannot be underestimated because uncontrolled cell growth plays a particularly integral role in the progression of HCC. Indeed, several reports have shown that the expression of proliferating cell nuclear antigen (PCNA) and Ki-67 is significantly associated with HCC relapse (25,26). This is in contrast to colon cancer, where proliferative activity alone appears not to result in fatal events (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, for representative sections, we tried both methods and obtained higher Ki-67 LI when the pressure cooker was used (data not shown). The most recent study demonstrated the prognostic value of Ki-67 LI in HCC by multivariate analysis (King et al, 1998). However, it is strange that they could not establish any correlation between the LI and clinicopathological features, because cell-proliferating activity should contribute greatly to the biological aggressiveness of carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, microscopy was performed by counting 41000 tumorous cells in a randomly selected highpower field (106100) from different representative parts of the tumor. Ki-67 expression level was grouped as high if 20% tumorous cells were Ki-67 positive, and as low if staining was 520% as described (King et al, 1998). As a result, HCCA1 expression level was closely correlated with the Ki-67 index (P50.01).…”
Section: Expression In Hcc Tissues and Clinicopathological Significancementioning
confidence: 97%